The good son [large type] - Mitchard, Jacquelyn (Thorndike Press large print core series., 2022)
"Stefan was just seventeen with he went to prison for the drug-fueled murder of his girlfriend, Belinda. Three years later, he's released to a world that refuses to let him move on. Meanwhile Thea Demetriou struggles to understand her son. At times, he is still the sweet boy he has always been; at other, he is a young man tormented by guilt and almost broken by his time in prison. But as his efforts to amends meet escalating resistance and threats, Thea suspects more forces are at play than just community outrage. And it there is so much she never knew about her own son, what other secrets has she yet to uncover--especially about the night Belinda died?"--